Unfit to Be a Slave: A Guide to Adult Education for Liberation - Vucaj, Indrit (Journal of Interdisciplinary Studies in Education, 2019)
Influenced by a mainstream radical ideology, Unfit to Be a Slave: A Guide toAdult Education for Liberation is unequivocally a democratic pillar of humanconsciousness. Unorthodoxy slants encouraging adult education as the locomotive to fithuman consciousness into a capitalistic design are dissed at best. The authorunapologetically calls for embracement of a new and radically revolutionary tenet aimedto liberate from captivity the conscious minds of human beings and seriously question thevery foundation of the role of education in the lives of human beings. Humanistic andlibertarian adult educators alike including liberals to some extent, who uphold the dignityand the autonomy of human beings (Elias & Merriam, 2005), appreciate the language andthe tone the author uses throughout the text in support to human empowerment.